MODEL KOMUNUIKASI INTERPERSONAL SPONSOR DENGAN CALON PEKERJA MIGRAN KABUPATEN CILACAP PADA SAAT REKRUITMEN - Hanifah Muyasaroh (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
The recruitment of prospective Indonesian migrant workers in Cilacap Regency is still being carried out by sponsors (brokers). In fact, after the promulgation of Law No. 18 of 2017 and published of PP No 59 about the Implementation of Protection for Indonesian Migrant Workers, the recruitment of prospective migrant workers is carried out by Indonesian Migrant Worker Placement Companies, hereinafter referred to as P3MI, which of course has a branch in the City District. Interpersonal communication as a communication model used by brokers in Cilacap Regency to carry out recruitment, greatly influences the attitudes and decisions of prospective migrant workers to work as migration. This research method uses qualitative analysis. The result of this research is that there is a symbiosis of mutualism, or to be precise, there is a dependency of prospective migrant workers on brokers because they are blind about everything about work migration procedures.